Perbandingan Hasil Pemilihan Smartphone Menggunakan Metode SMART, VIKOR, dan MAUT dalam Sistem Pendukung Keputusan - Syam, Syahriani; Muryanah, Siti (UNISTEK, 2025)
Selecting the right smartphone is a challenge for consumers due to the wide variety of product alternatives and the complexity of evaluation criteria such as price, technical specifications, and additional features. To address this issue, a systematic approach is needed through a Decision Support System (DSS) based on Multi-Attribute Decision Making (MADM) methods. This study aims to compare the results of smartphone selection using three MADM methods: SMART (Simple Multi Attribute Rating Technique), VIKOR (VIšekriterijumsko KOmpromisno Rangiranje), and MAUT (Multi Attribute Utility Theory). Smartphone alternatives were evaluated using six main criteria: price, battery capacity, camera quality, performance (RAM and processor), additional features, and 5G support. Each method was applied independently to generate a final ranking of the best smartphone. This research resulted in 1). A3 (Vivo V40 5G) with a value of 0.850 according to the SMART method, 2). A1 (Samsung Galaxy S24 Ultra) with a value of 0 according to the VIKOR method, and 3). A1 (Samsung Galaxy S24 Ultra) with a value of 0.925 according to the MAUT method. The results show variations in ranking across the three methods, indicating differences in their calculation approaches and sensitivity to weight distribution. This study provides a comprehensive analysis of the strengths and limitations of each method and highlights their relevance in supporting rational and need-based smartphone purchasing decisions. The findings can serve as a valuable reference for developers of recommendation systems and for consumers in making more informed choices.